Thermoelastic Properties of Nickel from Molecular Dynamic Simulations (Journal of Atomic and Molecular Sciences, 2018)
The structures and elastic constants of face-centered-cubic (fcc) structured nickel at high temperature have been calculated for the first time using molecular dynamics (MD) with the direct method and the quantum Sutton-Chen (Q-SC) potential. The obtained thermoelastic constants are in excellent agreement with the experiment data. Calculated results for the radial distribution function show that the short-range atomic order of low-$T$ is similar to the high-$T$ solid with the applied temperatures. The thermoelastic constants, the bulk and shear modulus as a function of the applied temperature are presented. An analysis for the calculated parameters has been made to reveal mechanical stability of nickel up to 1300 K.
Keywords: elastic properties; molecular dynamics; nickel.